1999
DOI: 10.1902/jop.1999.70.6.610
|View full text |Cite
|
Sign up to set email alerts
|

Opsonophagocytic Effect of Antibody Against Recombinant Conserved 40‐kDa Outer Membrane Protein of Porphyromonas gingivalis

Abstract: We conclude that antibody against r40-kDa OMP has opsonic activity on human neutrophil function for phagocytosis of P. gingivalis. Subgingival bacteria are coated in vivo with immunoglobulin and complement. When the antibody is specific for crevicular bacteria, immunological interactions can be expected in the crevice. Our observations suggest that the anti-recombinant 40-kDa OMP antibody in concert with the crevicular complement may prevent P. gingivalis colonization r40-kDa OMP may contribute to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Despite this, there are no vaccines in use for the prevention of adult periodontitis. Because P. gingivalis is a significant periodontal pathogen, investigators have assessed the potential of several P. gingivalis antigens to function as vaccine candidates, including killed whole P. gingivalis organisms and specific P. gingivalis antigens such as fimbriae, fimbrillin peptides, gingipains, hemagglutinins, and others (7,9,11,13,22,29,31). A conjugate vaccine consisting of P. gingivalis CPS and P. gingivalis fimbriae was shown to prevent P. gingivalis infection when a murine subcutaneous challenge model was used (6).…”
mentioning
confidence: 99%
“…Despite this, there are no vaccines in use for the prevention of adult periodontitis. Because P. gingivalis is a significant periodontal pathogen, investigators have assessed the potential of several P. gingivalis antigens to function as vaccine candidates, including killed whole P. gingivalis organisms and specific P. gingivalis antigens such as fimbriae, fimbrillin peptides, gingipains, hemagglutinins, and others (7,9,11,13,22,29,31). A conjugate vaccine consisting of P. gingivalis CPS and P. gingivalis fimbriae was shown to prevent P. gingivalis infection when a murine subcutaneous challenge model was used (6).…”
mentioning
confidence: 99%
“…However, the role of Fc␣RI and Fc␥RI in the pathogenesis of periodontitis remains unclear. As an approach to enhancing anti-P. gingivalis PMN function or to inhibiting colonization, major attention has been focused on local passive immunization with polyclonal antibodies or monoclonal antibodies (MAb) (3,28,47). It is therefore important to clarify the relative contributions of IgG and IgA receptors in triggering the anti-P. gingivalis function of GCF PMN.…”
mentioning
confidence: 99%
“…Further, these monoclonal antibodies possess complement-mediated bactericidal activity to P. gingivalis (17,18). Moreover, a recent study has demonstrated that these antibodies have opsonic activity on human neutrophil function for phagocytosis of P. gingivalis (19). Taken together, these findings suggest that 40k-OMP can be considered as a candidate antigen for the development of an antiperiodontitis vaccine.…”
Section: Discussionmentioning
confidence: 80%
“…Further, these monoclonal antibodies possess a complement-mediated bactericidal activity to P gingivalis (17,18). It has also been demonstrated that anti40k-OMP antibody opsonizes P gingivalis as a target for phagocytosis by the human neutrophil cell line (19). Finally, an interesting study has shown that the human monoclonal antibody against r40k-OMP generated by immunization of severe combined immunodeficiency mice that had been injected with human peripheral blood lymphocytes with r40-k-OMP inhibits coaggregation of P. gingivalis vesicle with Actinomyces naeslundii (20).…”
Section: Introductionmentioning
confidence: 99%